PELAYANAN KREDIT MULTIGUNA (KMG) TERHADAP CUSTOMER SATISFACTION PADA PT. BANK DKI KANTOR CABANG PEMBANTU DEWI SARTIKA - Amanda Puspitasari, Putri; Ariwibowo, Prasetio; Anita, Tri (Sekolah Tinggi Ilmu Ekonomi GICI, 2023)
This study aims to determine the problems or obstacles that result in a decrease in multipurpose loan applications (KMG) and determine strategies to increase the number of multipurpose loan customers at PT Bank DKI KCP Dewi Sartika. The strategy used in increasing the number of customers is a marketing strategy. The research method used in this study is a qualitative method using a type of descriptive research. Data collection method is carried out by conducting field documentation and interviews. The obstacle or problem found at Bank DKI KCP Dewi Sartika is the lack of employee service for multipurpose loan applications which resulted in a decrease in multipurpose loan applications. The resolution strategy to face the problems that occur is to carry out digital marketing strategies and carry out policies, namely Bank DKI KCP Dewi Sartika to improve services on multipurpose loans. The results showed that multipurpose loan disbursement increased from January 2021 to December 2021 to January 2022 to December 2022 with a percentage of 88% and affected services which also increased.